Uma visão teórica do 'psicodiagnóstico', de Rorschach - Novais, Jose (1979)
In this study theoretical approach to Hermann Rorschach's 'Psichodiagnostic' is attempted. On tries to point out that the theoretical basis of thest, in its origin, predetermines to a certain extent its paths of conceptual development. This permited its handling by means of points of view closes to thse basis. At the same time, it hinder and even prevent the full acceptance of the technique by conceptions and theories wich remote from its theoretical origins. To accomplish this, short retrospect of the test is made, as it arouse in the author’s min, with the permitive conceptual basis, in addiction to the history of its development and use by psychologist, physisians, and others professionals. This follow by how the leading theoretical systems in contemporary psychology approached the test. Thus, it is evaluated according to psychoanalysis, gestaltism, behaviorsm and psychometry, phenomenology and existencialism, and psycholinguistics. Concluding, on try to show the conceptual basis given to the test by the author, although considered not fully developed by scholars, ser certain definite limits to its evolution and theoretical approach, in such a way that objective conceptions, like behaviorism and psychometry, lay outside these limits. This prevent the test to be assimilated by these systems.